Optimalisasi Potensi Home Industry melalui Digitalisasi Marketing (Kasus: Produksi Emping Rumahan Kampung Pagutan, Desa Sukakerta, Cianjur) - Muhammad As’ary; Parhan Mugini; Muhammad Fikri Fakhrurozi; Sugiarti Sugiarti; Garnieta Febrianty Utami; Dwi Retno Hapsari (Jurnal Pusat Inovasi Masyarakat (PIM), 2021)
Emping is a kind of Indonesian snack or snack in the form of chips made from melinjo seeds. The abundance of these chips is an opportunity to become a business. However, the pandemic has hampered the marketing of the chips. IPB Goes To Field is present as a program that facilitates students to be able to directly help the community in answering the problems it faces. Data collected through interview methods and direct observation to related partners to determine the natural conditions and conditions of the community around the partner's residence. Research shows that the increase in online media marketing is a great opportunity to develop the chip selling market. In addition, the taste innovation in chips is also enjoyed by various groups. The optimization is in the form of canvas model business training, digital marketing and procurement of media and business support equipment. Keywords: business, digitalization, emping